PENGEMBANGAN MODUL PEMBELAJARAN SOSILOGI BERMEDIA VISUAL MAHASISWA STIKES HARAPAN IBU JAMBI - Hamdani, Hamdani; Khairinal, Khairinal; Emosda, Emosda (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2013)
This study aims to develop a sociology of media visual learming modules that can facilitate learning students in sociology courses. The use of sociology of learning modules developed have special guality compared with not using a module, so as to facilitate student learning sociology courses. Researeh is the development of Dick and Carey model as for the procedures in the development of this research are as follows: analysis of the potential and problems, data collection, productdesign, product validation, 2 (two) experts are skilled instructional design and materials expert, and then implement the revised of the design has been validated, tested on a limited group, has revised the product, conduct field trials, and then revise the product back, and the final stage is a product of module development sociology. The results showed that the overall learning modules developed having good criterion with an average of 3.88 based upon the response and course student learning outcomes of public health sciences major goals in learning.The results can be concluded that the learning module that was developed a learning module using visual media for teaching sociology is easy to use as a learning module on the subject of sociology studies of public health sciences programmed STIKES Harapan Ibu Jambi. As for the suggestions from the results of data analysis in this development was before the development of learning modules mediated visual sociology, should show the problems that have public health science study programs so that the resulting product can be optimally used and for further development, preferably in added the material development of learning modules using visual media.